2015
DOI: 10.1021/acs.macromol.5b01813
|View full text |Cite
|
Sign up to set email alerts
|

Photomechanical Energy Transfer to Photopassive Polymers through Hydrogen and Halogen Bonds

Abstract: The supramolecular assembly of photoactive azobenzenes with passive polymers via halogen or hydrogen bonding is a cost-effective way to design materials for various photomechanical applications that convert light energy directly into macroscopic motion, for instance, in all-optical surface patterning and photochemical imaging of plasmonic structures. To elucidate the molecular-level origins of this motion, we show, by coupling dynamic infrared spectroscopy to a photo-orientation setup, that supramolecular bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 48 publications
5
47
0
Order By: Relevance
“…25 The benefits of halogen bonding, such as the high directionality and tunability, 2628 have recently been recognized in the design of functional materials. 29,30 In particular, halogen-bonded, azobenzene-containing co-crystals 3133 and (amorphous) supramolecular side-chain polymers 34,35 have shown extremely interesting photoresponsive properties, even superior to their hydrogen-bonded counterparts. Since the first demonstration in 2004, 36 several halogen-bonded LCs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…25 The benefits of halogen bonding, such as the high directionality and tunability, 2628 have recently been recognized in the design of functional materials. 29,30 In particular, halogen-bonded, azobenzene-containing co-crystals 3133 and (amorphous) supramolecular side-chain polymers 34,35 have shown extremely interesting photoresponsive properties, even superior to their hydrogen-bonded counterparts. Since the first demonstration in 2004, 36 several halogen-bonded LCs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our studies indicate that phenolic hydrogen bond and iodoacetylenebased halogen bond with poly(4-vinylpyridine) (P4VP) are relatively stable upon trans-cis-trans cycling. 84 Such studies, assessing the photostabilities of different supramolecular bonds, should be extended, for instance, to different temperatures. Yet already the first experiments 85 highlight that supramolecular bonds are effective for kinetic energy transfer between the phototoactive azobenzene units and the photopassive polymer.…”
Section: Characterization Of the Supramolecular Bondmentioning
confidence: 99%
“…This was attributed to the much higher orientation of the halogenfunctionalized azo unit, which in turn was related to the higher T g of the halogen-bonded complex. 84 The advantage of the more directional nature of halogen bonding has also been pointed out in nonlinear optics. A simple mutation of the halogen from iodine to bromine in halogen-bonded azobenzene-P4VP complexes more than doubled second-harmonic generation upon all-optical poling of the materials.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Supramolecular material design, which employs spontaneously forming noncovalent bonds, such as hydrogen and halogen bonding, between photoactive azobenzenes and photopassive polymers, provides a window of opportunity to delve more deeply into the question of main chain versus side group orientation, since it is easy to prepare supramolecular assemblies with variable spacer lengths, including spacer‐free structures. By applying polarization modulation infrared structural absorbance spectroscopy (PM‐IRSAS)—a method derived from PM‐IRLD that, in addition, is capable of recording the absolute parallel and perpendicular absorbance spectra simultaneously, and thus can determine the structural absorbance spectrum and quantify the photo‐orientation in situ—we demonstrated that the larger photo‐orientation of iodoacetylene‐capped halogen‐bonded azobenzenes compared to their hydrogen‐bonded and nonbonded analogues leads to larger photo‐orientation of the passive pyridine moiety of the poly(4‐vinylpyridine) host but to no orientation of the main chain . IR spectroscopy further allows distinguishing the occupied and free pyridine moieties in these supramolecularly bonded complexes.…”
Section: Photo‐orientation Of Azobenzenes and Photocontrol Of Passivementioning
confidence: 99%